Diagnosis of the Energy Regulatory Scenario with Emphasis on Smart Energy - Carvalho, Patricia Stefan de; Siluk, Julio Cezar Mairesse; Oliveira, Henrique Luís Sauer; Garcia, Vinicius Jacques; Schaefer, Jones Luís; Cassel, Ricardo Augusto; Pinheiro , José Renes (International Journal of Energy Economics and Policy, 2024)
The energy management system has evolved into a digitized and autonomous environment, where consumers can manage their own generation, consumption and storage through virtual environments. Smart Energy (SE) understands this decentralized energy management by streamlining and helping in this matter, however, there is a need to regulate this scenario. Considering that the electric energy sector has a solid regulation, efforts need to be concentrated to adapt it to a model that emphasizes the SE and everything that it proposes. Therefore, the objective of this article is to propose a diagnosis of the current energy regulatory scenario directed to the SE. Through a focus group, experts from the energy sector contributed with opinions on the subject for the construction of a Current Reality Tree (CRT), which aimed to identify the root causes that affect and limit the energy regulation scenario SE-oriented. The current situation of this scenario was analyzed and what can be changed. 38 actions that contribute to the development and propagation of SE were suggested. These actions are guiding ways to regulate and enable the regulatory environment to support the insertion of technologies related to the theme.